Impact of Lack of Social Support on Mental Health and Academic Achievement Among International Students in United State - Al-Juaid, Asma Mubarak (Journal of Humanities & Social Sciences, 2019)
This study aimed to reveal the impact of lack of social support on mental health and academic achievement, and to determine associations of social support between depression and academic achievement, among international students in U.S. universities. The researcher used the systematic review approach and all literature that related to the research’s subject was scanned and analyzed to achieve the aims of the study.The study indicated that international students in the United States experienced cultural, social, or environmental stressors which resulted in internal difficulties. It also showed that international students who did have access to social support from family, friends, and teachers achieved higher grade point averages, as for the academic stress faced by international students in the United States was also shown to be substantially higher than that faced by native U.S. students.
Keywords: depression; social support; international students; mental health; academic performance